Desempenho eletroquímico e caracterização de compósitos condutores MnCo2O4,5@PPi, Bi2O3@PPi e NTC@Ppi como eletrodos em supercapacitores - Xavier, Fárlon Felipe Silva (2018)
The coatings of microstructure and nanostructure materials are alternative for electrodes in supercapacitors with significant increases in values of energy-storage capacity. In the present work the MnCo2O4,5, Bi2O3 particles and carbon nanotubes (CNT) coated by polypyrrole (PPy) and the influence on the electrochemical properties of the resulting composites for application in hybrid capacitors was investigated. The X-ray diffractograms of the oxides showed well-defined diffraction peaks, which were indexed to the cubic phase of MnCo2O4,5, and to the monoclinic phase to α-Bi2O3. SEM images showed oxide particles (MnCo2O4,5, α-Bi2O3) and CNT coated by PPy. From the electrochemical characterization techniques, it can be concluded that the composites showed an intensification of their properties with values of specific capacitance (~510.40 F g-1), specific power (~16.66 kW kg-1), specific energy (~163.33 W h kg-1) and coulomb efficiency (~96.30%). Therefore, hybrid composites are promising materials as electrodes in hybrid capacitors.